Effect of Intermittent Traveling Water Screen Operation on Fish Survival. (11th October 2021) - Rackovan, Jenna; Zottoli, Joe; Amaral, Stephen V.; Black, Jonathan; McMahon, Brian
Abstract: The U.S. Environmental Protection Agency's final rule for complying with section 316(b) of the Clean Water Act states that cooling water intakes withdrawing >7.6 million liters per day must use one of seven alternatives to reduce fish impingement mortality. Fish‐friendly traveling water screens (TWSs) are expected to be frequently utilized because of relative ease of retrofit. The final rule requires "continuous or near continuous screen rotation" to facilitate recovery of collected fish as soon as practical. However, intermittent TWS operation could be advantageous for operators because reductions in screen system operating time will extend equipment life and reduce operating costs. A laboratory evaluation was conducted with Golden Shiner Notemigonus crysoleucas, Bluegill Lepomis macrochirus, Largemouth Bass Micropterus salmoides, and Common Carp Cyprinus carpio (42–106 mm TL) to determine whether intermittent rotation would optimize TWS operation and maintain biological performance. A preliminary evaluation was conducted with three approach velocities (0.30, 0.45, and 0.60 m/s) at four stationary screen durations (2, 4, 6, 12 h) in small test flumes to select parameters for a larger‐scale evaluation. The full‐scale evaluation tested two approach velocities (0.30 and 0.45 m/s) at two stationary durations (2 and 4 h at 0.45 m/s; 6 and 12 h at 0.30 m/s) and continuous screen operation. Fish avoided impingement at 0.30 m/s, and approach velocity was the primary determinant of survival probability, with increased velocity leading to increased mortality. Severe injuries occurred more frequently during stationary screen trials than with continuous operation; over 50% of fish had >40% scale loss at 0.45 m/s for stationary trials. The results indicate that continuous rotation is optimal for fish survival at approach velocities between 0.30 and 0.45 m/s. However, intermittent operation at average approach velocities of 0.30 m/s or less may be acceptable for fishes with equal or greater swimming ability than those tested in this study.